Optimasi Sistem Pull Kanban untuk Mitigasi Kerusakan Material Daur Ulang di CV. XYZ - Rulaa Zhalfa Shafira; Wiku Larutama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. XYZ is an industry that produce ropes made from recycled yarn as its primary raw material. This material is highly susceptible to degradation when stored for extended periods. The current push system leads to excessive inventory accumulation, increasing the risk of material deterioration. This study aims to optimize a pull system using the Kanban method to control raw material storage time. A quantitative approach was employed by analyzing historical demand data from October 2024 to October 2025. The number of Kanban cards was determined based on average daily demand, lead time, safety factor, and Bill of Materials (BOM) analysis. The results indicate an average raw material requirement of 68 kg per day. The optimization produced 13 Kanban cards, allocated into 8 cards for base yarn and 5 cards for variant yarn. The implementation reduced average material dwell time to 4.78 days. The Kanban pull system effectively mitigates raw material deterioration while improving material flow responsiveness to demand fluctuations.